Synthesis and biological evaluation of 5-fatty-acylamido-1, 3, 4-thiadiazole-2-thioglycosides. Issue 15 (1st August 2017) - Vudhgiri, Srikanth; Koude, Dhevendar; Veeragoni, Dileep Kumar; Misra, Sunil; Prasad, R.B.N.; Jala, Ram Chandra Reddy
Graphical abstract: Abstract: In the present study, the synthesis of 1, 3, 4-thiadiazole-based thioglycosides were accomplished in good yields with employing a convergent synthetic route. The starting material 5-amino-1, 3, 4-thiadiazole-2-thiol and followed by a series of 5-fatty-acylamido-1, 3, 4-thiadiazole-2-thiols (4a–4j ) were synthesized with different fatty acid chlorides. The glycosylation of compounds4a–4j were achieved with trichloroacetimidate methodology. Antimicrobial and cytotoxicity activities of title compounds were evaluated. Among the entire compounds lauric acid and myristic acid derivatives showed good and moderate antimicrobial activity. In case of cytotoxicity results of compounds8a–8j and9a–9j, the acetate protected short chain (C6:0, C8:0, C10:0) compounds and the free hydroxyl long chain saturated (C16:0, C18:0) and unsaturated (C18:1, C22:1) compounds exhibited good activity against different cancer cell lines. Further, the free hydroxyl compounds9a, 9c–9j did not show any toxicity towards normal CHO-K1 cell line whereas acylated compounds8a–8j exhibited toxicity.